Test-retest reproducibility of echocardiography and CMR in the same patients for assessing left atrial function. (4th February 2022) - Alfuhied, A; Gulsin, GS; Brady, EM; Yeo, JL; Parke, K; Marsh, AM; Arnold, JR; Mccann, GP; Singh, A
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia Background:  Cardiovascular magnetic resonance (CMR) has been shown to give higher left atrial (LA) volumes than trans-thoracic echocardiography (TTE) but the agreement and test-retest reproducibility of LA functional measure have not been directly compared in the same patient cohort. Methods:  People with type 2 diabetes mellitus (T2D) without cardiovascular disease underwent TTE and CMR on the same day on two separate occasions with a mean period of 11± 4 days. TTE images were analysed using TomTec-ARENA (v2.4, 2D-CPA), where Medis Suite (v3.1, medical imaging system) was used for CMR images. The analysis included LA strain, corresponding to LA reservoir, conduit, and booster pump (contraction function), LA volumes, and LA emptying fraction (LAEF), which was calculated using area length method. Strain and volume were assessed on 4- and 2-chamber long-axis and average values were calculated for both modalities. Results:  10 participants with T2D (mean age 65.6 ± 7.3 years, 50% male) were studied. CMR LA volumes were significantly higher and LAEF significantly lower compared to TTE (P < 0.01 for all), whilst reservoir strain on CMR was lower compared to TTE (29.2 ± 6.5 vs 33.8 ± 3.7, p = 0.04).  The inter-modality agreement was moderate for LA volumes and contraction strain (ICC ≥0.55) and poor for LAEF, strain at reservoir and conduit. Overall, the test-retest reproducibility of CMR was higher than for TTE, but the overall limits of agreement were not too dissimilar on Bland-Altman analysis (Table & Figure). TTE reproducibility was good for LA volumes and strain at conduit (CoV 18-24%, ICC ∼0.80) and moderate for LAEF, strain at reservoir and contraction. CMR showed excellent test-retest reproducibility for LA volumes, EF and strain at reservoir (CoV 7-20%, ICC ≥0.83). Conclusion:  The test-retest reproducibility of CMR is slightly better than TTE for LA assessment using volumes and strain. LA volumes have superior reproducibility compared to functional LA parameters.